Patterns of self-intoxication among inpatients in Benghazi medical center – Libya - Muftah S Elsaeiti; Soad I Alkhumsi; Khaled D Alsaeiti (Apollo Medicine)
Background: Self-harm is a major public health concern, with community studies reporting a lifetime risk of 13%–18%, it is a key risk factor for suicide, and it is important to have contemporary information on the extent of risk and is relatively common among young people with prevalence rates in adolescent samples which range from 6.9% to 15.9%. One review of the literature showed that 13.2% of adolescents reported engaging in self-harm at some stage in their lives. The aim of this study was to describe the characteristics patterns of self-intoxication patients and their response to psychiatric consultation. Patients and Methods: This observational single-center study involved prospective review of all patients whom admitted to the Medical Department at Benghazi Medical Center over a 12-month period from January 2017 to December 2017 after self-intoxication. Self-intoxication with suicidal intent was assessed in the emergency department after questioning of the patient and relatives. Data included were age, sex, marital status, employment, type and source of drugs or toxins, and whether the material was taken intentionally or accidentally. Patients who were considered to have an accidental overdose or drug mistake were not included in the study. Results: Sixty-six patients were identified, 53 (80%) were females with a mean age of 23 years, 49 (74%) were single, and all males were jobless and school-leavers. Twenty-nine (55%) females were homemakers, 19 (36%) were students, and 9% were working. Fifty-seven (86%) get the drugs from their home, 9 (14%) bought from the market, 55 (83%) took the drug intentionally, and 11 (17%) accidentally. Thirty (45%) used drugs as toxins, 22 (33%) insecticides, 10 (5%) rat killers, and 4 (6%) other types of toxins. Nine (14%) were admitted to the intensive care unit, 38 (58%) refused any psychiatric consultation. Conclusions: Causes are associated with both individual and socioeconomic parameters, such as relationships among family members, unemployment, insufficient education, and drug misuse. Due to the repeated drug intoxication events, it is obvious that these persons definitely need psychiatric help and support.